Fragment-based design, synthesis, biological evaluation, and SAR of 1H-benzo[d]imidazol-2-yl)-1H-indazol derivatives as potent PDK1 inhibitors. Issue 24 (15th December 2017) - Chen, Ting; Sorna, Venkataswamy; Choi, Susie; Call, Lee; Bearss, Jared; Carpenter, Kent; Warner, Steven L.; Sharma, Sunil; Bearss, David J.; Vankayalapati, Hariprasad
Graphical abstract: Abstract: In this work, we describe the use of the rule of 3 fragment-based strategies from biochemical screening data of 1100 in-house, small, low molecular weight fragments. The sequential combination of in silico fragment hopping and fragment linking based on S160/Y161/A162 hinge residues hydrogen bonding interactions leads to the identification of novel 1 H -benzo[ d ]imidazol-2-yl)-1 H -indazol class of Phosphoinositide-Dependent Kinase-1 (PDK1) inhibitors. Consequent SAR and follow-up screening data led to the discovery of two potent PDK1 inhibitors: compound32 and35, with an IC50 of 80 nM and 94 nM, respectively. Further biological evaluation showed that, at the low nanomolar concentration, the drug had potent ability to inhibit phosphorylation of AKT and p70S6, and selectively kill the cancer cells with mutations in both PTEN and PI3K. The microarray data showed that DUSP6, DUSP4, and FOSL1 were down-regulated in the sensitive cell lines with the compound treatment. The in vivo test showed that35 can significantly inhibit tumor growth without influencing body weight growth. Our results suggest that these compounds, especially35, merit further pre-clinical evaluation.